New taxonomic data on Zodariinae (Araneae: Zodariidae) of Azerbaijan, Iran, Afghanistan and Pakistan - Zamani, Alireza; Marusik, Yuri M. (Zootaxa, 2022)
New taxonomic considerations on several species of the zodariid spider subfamily Zodariinae Thorell, 1881 occurring in Azerbaijan, Iran, Afghanistan and Pakistan are presented. Three species, Trygetus cyrus sp. n. (♀; Fars, south-central Iran), T. nakhchivanicus sp. n. (♂; Nakhchivan, Azerbaijan) and Zodarion sharurensis sp. n. (♂♀; Nakhchivan, Azerbaijan) are described as new, and the hitherto unknown male of Trygetus susianus Zamani & Marusik, 2021 is described based on topotype material from Khuzestan, southwestern Iran. Indozodion Ovtchinnikov, 2006 stat. rev. is rediagnosed and removed from the synonymy of Tropizodium Jocqué & Churchill, 2005, and here considered to comprise I. inayatullahi Ovtchinnikov, 2006 comb. rev. (type species) and I. lindbergi (Roewer, 1960) comb. n. (ex. Zodarion Walckenaer, 1826); the latter species, previously known only from Afghanistan, is redescribed and reported from Pakistan. One of the paratypes of I. lindbergi, reported as a subadult female in the original description, is found to be an adult female of Parazodarion raddei (Simon, 1889). An error in a previous publication (attributing figures of Acanthinozodium elburzicum Zamani & Marusik, 2021 to P. raddei) is also corrected here.